Research on the impact of digital inclusive finance development on the consumption gap between urban and rural residents - Zhang, Yu; Xiong, Xue; Chen, Yiling (Edelweiss Applied Science and Technology, 2025)
This study employs panel data from 31 provinces across China spanning the period from 2011 to 2023 to conduct an empirical examination of the impact of digital inclusive finance on the urban-rural consumption gap and its underlying mechanisms. The findings reveal that digital inclusive finance has a significant effect in narrowing the urban-rural consumption gap. Specifically, for every one-unit increase in the digital inclusive finance index, the urban-rural consumption gap decreases by 0.1688 units. Through the mediation effect test, it is demonstrated that digital inclusive finance indirectly achieves the outcome of reducing the consumption gap by enhancing residents' income levels. Heterogeneity analysis further unveils a differentiated pattern in the inclusive effects of digital inclusive finance across regions: its effect in narrowing the urban-rural consumption gap is more pronounced in areas with higher urbanization rates and municipalities directly under the central government, whereas the corresponding effect is relatively weaker in regions with lower urbanization rates and ordinary provinces. Based on these research findings, this paper proposes relevant recommendations. It is suggested to refine a differentiated financial support system centered on upgrading the rural consumption structure, while concurrently strengthening the development of digital infrastructure and risk prevention and control efforts. These measures are aimed at facilitating a gradual transition from a mere quantitative pursuit of urban-rural consumption convergence towards a balanced qualitative development, thereby establishing a sustainable policy focal point for the realization of common prosperity.